Health services for children in western Europe. - Wolfe, I; Thompson, M; Gill, P; Tamburlini, G; Blair, M; van den Bruel, A; Ehrich, J; Pettoello-Mantovani, M; Janson, S; Karanikolos, M; McKee, M (2013)
Western European health systems are not keeping pace with changes in child health needs. Non-communicable diseases are increasingly common causes of childhood illness and death. Countries are responding to changing needs by adapting child health services in different ways and useful insights can be gained through comparison, especially because some have better outcomes, or have made more progress, than others. Although overall child health has improved throughout Europe, wide inequities remain. Health services and social and cultural determinants contribute to differences in health outcomes. Improvement of child health and reduction of suffering are achievable goals. Development of systems more responsive to evolving child health needs is likely to necessitate reconfiguring of health services as part of a whole-systems approach to improvement of health. Chronic care services and first-contact care systems are important aspects. The Swedish and Dutch experiences of development of integrated systems emphasise the importance of supportive policies backed by adequate funding. France, the UK, Italy, and Germany offer further insights into chronic care services in different health systems. First-contact care models and the outcomes they deliver are highly variable. Comparisons between systems are challenging. Important issues emerging include the organisation of first-contact models, professional training, arrangements for provision of out-of-hours services, and task-sharing between doctors and nurses. Flexible first-contact models in which child health professionals work closely together could offer a way to balance the need to provide expertise with ready access. Strategies to improve child health and health services in Europe necessitate a whole-systems approach in three interdependent systems-practice (chronic care models, first-contact care, competency standards for child health professionals), plans (child health indicator sets, reliable systems for capture and analysis of data, scale-up of child health research, anticipation of future child health needs), and policy (translation of high-level goals into actionable policies, open and transparent accountability structures, political commitment to delivery of improvements in child health and equity throughout Europe).